Testing the Role of Environmental Harshness and Sexual Selection in Limb Muscle Mass in Anurans - Yang, Yue Jun; Jiang, Ying; Mi, Zhi Ping; Liao, Wen Bo (Frontiers in Ecology and Evolution, 2022)
Sexual dimorphism is regarded as the consequence of differential responses by males and females to selection pressures. Limb muscles play a very important role during amplexus, which is likely to be under both natural and sexual selection in anurans. Here, we studied the effects of natural and sexual selection on limb muscles mass in males and females across 64 species of anurans. The results showed that there were non-significant differences in relative limb muscles mass between the sexes among species, exhibiting no sexual dimorphism in limb muscles. Absolute and relative limb muscles mass positively displayed correlations with SVL for both sexes. However, neither male-biased operational sex ratio nor environmental harshness (e.g., CV in temperature and CV in rainfall) can explain relative limb muscles mass (e.g., forelimb, hindlimb and total limb muscles) within each sex. The findings suggest that environmental harshnessnatural and sexual selection cannot play important roles in promoting variations in limb muscles among anuran species.